Meningkatkan Motivasi dan Hasil Belajar PKn Siswa Materi Mengevaluasi Berbagai Sistem Pemerintahan Menggunakan Model Pembelajaran Kooperatif Tipe Jigsaw pada Kelas XII Akuntansi 2 SMK Bina Banua Banjarmasin Tahun Pelajaran 2014/2015 - Misran, Misran (Jurnal Pendidikan Kewarganegaraan, 2015)
Causes of low student achievement in class XII SMK Bina BANUA Accounting 2 Banjarmasin is the lack of attention to students when the teacher explains the material in front, the lack of motivation in students learning, teachers are using lecture and question and answer. In addition, also, very rarely use cooperative learning model. Cooperative learning is an option because it can raise student motivation and learning outcomes. The aim of this study were: (1) Increasing student motivation in learning to use the Civic Education Cooperative learning model Jigsaw type Civics learning, (2) Improve student learning outcomes in Civics learning using Jigsaw cooperative learning model in teaching civics class XII student of Accounting 2 SMK Bina BANUA Banjarmasin Academic Year 2014/2015, (3) To determine the response of students to instructional materials with application macampemerintahan evaluate various learning models Jigsaw. Classroom action research carried out in the second cycle. Each cycle consists of four main activities: planning, action, observation / observation and reflection. Object class XII students study Accounting 2 SMK Bina BANUA Banjarmasin. Data collection is done by testing, observation, and questionnaires. Mechanical analysis of quantitative and qualitative data. The results of the study concluded that the application of jigsaw cooperative learning methods can increase the motivation to learn civics class XII student of Accounting 2 SMK Bina BANUA Banjarmasin 2014/2015 school year as evidenced by an increase in motivation to learn civics percentage score of 58.3% in the first cycle to 74, 6% in the second cycle, (2) use of Jigsaw cooperative learning model in the material system of government can improve student achievement, ie from 42.64 to 55.8% completeness in the first cycle, rising to an average of 75 with a classical completeness 97% in the second cycle.Keywords: motivation, learning outcomes Civics, models Jigsaw